2022
DOI: 10.3390/app12042060
|View full text |Cite
|
Sign up to set email alerts
|

Experiment and Research on Cutting Mechanical Properties of Little Cabbage

Abstract: To reduce the cutting force and cutting power consumption during harvest, the cutting mechanical properties of the root of little cabbage were studied. The cutting experiment was carried out using a texture analyzer, and the influence of the individual factors, the cutting bevel angle, the sliding angle, and the cutting gap on the maximum cutting stress and specific cutting energy were studied, respectively. On the basis of single factor experiments, multi-factor experiments were carried out using the central … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…As provided in Table 7, the responses were obtained in the course of the cycle of studies (Sections 2 and 3) of cutting corn stalks harvested from the fields located in the Wielkopolska Province (west-central Poland); the value of the corn-stalk cutting force, F cc is primarily influenced by the blade angle, α, (Table 7) and this variable is the significant component of the model expressed in the form of Equation ( 4) in Section 3.1, as signified by the p-value of < 0.0001. Similarly, the studies of Wang et al [22] also demonstrated that the blade angle and its interaction with the distance between the blade and the counter blade (see Table 7) has the greatest influence on the process of energy consumption. Moreover, as provided in Figure 7, together with the increase in the linear velocity of the blade, V, we observe a decrease in the force value, F cc , for the entire range of values of the distance, g, and the blade angle, α.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…As provided in Table 7, the responses were obtained in the course of the cycle of studies (Sections 2 and 3) of cutting corn stalks harvested from the fields located in the Wielkopolska Province (west-central Poland); the value of the corn-stalk cutting force, F cc is primarily influenced by the blade angle, α, (Table 7) and this variable is the significant component of the model expressed in the form of Equation ( 4) in Section 3.1, as signified by the p-value of < 0.0001. Similarly, the studies of Wang et al [22] also demonstrated that the blade angle and its interaction with the distance between the blade and the counter blade (see Table 7) has the greatest influence on the process of energy consumption. Moreover, as provided in Figure 7, together with the increase in the linear velocity of the blade, V, we observe a decrease in the force value, F cc , for the entire range of values of the distance, g, and the blade angle, α.…”
Section: Discussionmentioning
confidence: 67%
“…A study of the cutting process of cabbage seedlings employing a counter-blade (supported cutting) was carried out by Wang et al [22]. The obtained results indicate that with the increase in the value of the blade rake angle, the cutting stresses and specific energy would initially decrease, and afterwards their values would increase.…”
Section: Introductionmentioning
confidence: 99%
“…Several attempts have been made to enhance implement and increase the efficiency of crop harvesting equipment and its cutting tools (Bochat et al., 2021; Cui et al., 2021; Dixit et al., 2012; D. Du & Wang, 2016; El Didamony & El Shal, 2020; Glaus et al., 1972; Hosseinpour‐Zarnaq et al., 2022; Huang et al., 2020; Lesani et al., 2018; Lima et al., 2021; Navas et al., 2020; Patel et al., 2018; Pellenc & Pellenc, 2014; Popa & Popa, 2020; Schmid, 1965; Shearer et al., 1991; Song et al., 2022; Taghinezhadet al., 2012; Tang et al., 2021; Vu, Ngo, et al., 2020b; W. Wang et al., 2022; Xie, Jin, et al., 2022; Xie, Wang, et al., 2022). One of the key factors in crop harvesting is cutting force (Ma et al., 2014; Preethi et al., 2021; Zein El‐den et al., 2020).…”
Section: Introductionmentioning
confidence: 99%